On stability and protonation of multielectron systems: The concept of proton affinity. II. Dissociative proton attachment and protonation-Deprotonation mapping - Kryachko, Eugene S. (International journal of quantum chemistry, 2012)
A few touches on the thematic palette “molecular protonation” directly linked to the concept of molecular stability have been accomplished. They are of different nature, of different origin, and taken from “different angles” of lighting; however, together, they definitely provide a sufficiently complete picture “The protonation interaction, as being strong enough, may break the stability of molecules subject to protonation.” © 2011 Wiley Periodicals, Inc. Int J Quantum Chem, 2012